Peningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS dengan Menggunakan Metode Cooperative Integrated Reading and Composition (CIRC) di Kelas III MI NW Taman Pagesangan Mataram - Rafikah, Ismu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this study was to know the improvement of students learning outcomes in Social Studies subject using Cooperative Integrated Reading and Composition (CIRC) method in Class III of MI NW Taman Pagesangan Mataram. The research method used was Classroom Action Research. This research was carried out in MI NW Taman Pagesangan and used 23 students as subjects of the research. Instruments of data collection used observation sheet, test, and documentation. Data analysis technique used descriptive qualitative and quantitative analysis technique by using the completeness test formula. The result of this study indicated that the application of Cooperative Integrated Reading and Composition method could improve Social Studies learning outcomes in class III of MI NW Taman Pagesangan. This was in accordance with the results of tests that had showed improvement on students learning outcomes from the first cycle test to the second cycle test. The students’ average test score of the first cycle was 80 and the students’ average test score of the second cycle test increased to 85. The completeness Classical score also experienced an increase from cycle I to cycle II, from 82.60% up to 91.30%.